Allocation of energy consumption and greenhouse gas emissions in the production of earthenware ceramic pieces - Quinteiro, Paula (2019)
The ornamental earthenware ceramic manufacturing is typically a multifunctional system because several pieces with different dimensions and geometries are produced in the same mill, at the same time. Therefore, an allocation procedure is needed in order to quantify the share that each ornamental earthenware ceramic piece represents in the manufacturing total energy consumption and costs and greenhouse gas (GHG) emissions. The main aim of this study was to present a methodology to allocate to each piece the energy consumed in the ornamental earthenware ceramic manufacturing process. The methodology relies on mass, volume or number of pieces, depending on the type of energy and stage of manufacturing, and has been tested and validated in a real manufacturing context at an ornamental earthenware ceramic mill. Another objective of this study was the determination of the energy consumption and cost and the GHG emissions, per piece, of some pieces produced in the mill where the allocation methodology was applied, in order to identify improvement opportunities in the manufacturing process. The results show that the energy consumption and costs and the GHG emissions of the studied ceramic pieces are strongly dependent on its dimension, both in terms of mass and volume, and also on the piece susceptibility to crack and to experience deformations and imperfections. These results suggested some improvement measures to reduce the consumption of electricity, natural gas (in shaping and in the biscuit and glost firing cycles) and calcite used as raw material.